HUMOUR IN BARACK OBAMA'S SPEECH: A CONVERSATION ANALYSIS (CA) - Niken Fatma Putri; Filia Filia (Universitas Islam Sumatera Utara (UISU), 2022)
Evaluation and critics are two essential aspects in assessing a perfect performance. Public speaking is a platform to convey critics as well as evaluations publicly. Critics and Evaluation is an embodiment of check and balance in a democratic nation. Barack Obama attends White House Association Correspondents Dinner annually as a sign of USA democracy establishment. This event is a mark of good relationship between government and mass media correspondents. This study finds critical and evaluative humorous utterances as Obama’s tactical strategy to deliver his critics and evaluation. This research is qualitative research that uses conversational analysis (CA) as the method. The data were transcribed by Jefferson transcription system (2020). It has an aim to examine implicature theory (Grice, 1975) further in humour. This study shows that pragmatical utterances, that is conveyed in humorous concept, need a construction of common understanding, named as common ground. Turn taking is seen from speaker’s speech and various responses of audiences such as laughter, applauses, or short verbal responses. These responses become essential part of discourse constructions in seizing its goal, to criticize and evaluate colleagues’ performance.